2013
DOI: 10.4172/2155-6156.1000286
|View full text |Cite
|
Sign up to set email alerts
|

The Prevention of Gestational Diabetes

Abstract: The negative impact of the gestational diabetes on the maternal and fetal health is well known and this impact is closely related to gestational age at which the diagnosis is done. Therefore, the use of therapeutic options able to prevent or delay the gestational diabetes occurrence has a positive impact on maternal and neonatal outcomes.Physical activity and dietary advice represent the first choice and they are the most studied as well. They represent a non-pharmacological option and have a positive impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 89 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…For example, chromium, another group six transition metal with a high melting point, is involved with the metabolism of glucose and insulin. 53,54 Furthermore, there could be sex-differences underlying the mechanisms relating urinary W to diabetes. For example, one study observed that the effect of W on bone homeostasis in mice was sex-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…For example, chromium, another group six transition metal with a high melting point, is involved with the metabolism of glucose and insulin. 53,54 Furthermore, there could be sex-differences underlying the mechanisms relating urinary W to diabetes. For example, one study observed that the effect of W on bone homeostasis in mice was sex-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on Cr deficiency indicate that chromium is an essential element involved in the action of insulin [67]. There is increasing evidence that Cr supplementation, especially in higher doses and in the form of free chromium, may improve insulin and glucose sensitivity in type 1 and 2 diabetes [70,71]. The 'Bristol' variety of black raspberry seems to be important in the prevention and treatment of metabolic diseases due to the high content of chromium, zinc and manganese, the deficiency of which is associated, among others, with the development of diabetes.…”
Section: Contents Of Macro-and Micro-elements In the Analysed Raspber...mentioning
confidence: 99%
“…Shilajit contains many trace elements including, chromium, potassium, magnesium, zinc, copper, iron, and many others (Mishra et al, 2019). Shilajit contains chromium, which is very important in carbohydrate and lipid metabolism and is recommended to be taken by diabetic patients; it increases insulin binding to its receptors; thus, it increases insulin sensitivity (Anderson, 2000). Taking a mixture of 12 herbs twice a day for 13 days in 10 diabetic patients, including Shilajit, significantly reduced the accumulative hemoglobin HbA1C (Pal & Shrivastav, 2020).…”
Section: Shilajit Studies On Diabetesmentioning
confidence: 99%